Image registration and image interpolation in volume rendering of cross sections - Castanho, Jose E C [UNESP]; Bellon, Olga R P [UNESP]; Tozzi, Clesio L. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1995)
We outline a method for registration of images of cross sections using the concepts of The Generalized Hough Transform (GHT). The approach may be useful in situations where automation should be a concern. To overcome known problems of noise of traditional GHT we have implemented a slight modified version of the basic algorithm. The modification consists of eliminating points of no interest in the process before the application of the accumulation step of the algorithm. This procedure minimizes the amount of accumulation points while reducing the probability of appearing of spurious peaks. Also, we apply image warping techniques to interpolate images among cross sections. This is needed where the distance of samples between sections is too large. Then it is suggested that the step of registration with GHT can help the interpolation automation by simplifying the correspondence between points of images. Some results are shown.
Keywords: Algorithms; Automation; Data acquisition; Data reduction; Image analysis; Image reconstruction; Interpolation; Mathematical models; Mathematical transformations; Probability; Three dimensional; Visualization; Generalized Hough transforms; Image interpolation; Image registration; Image warping techniques; Volume rendering; Volume visualization; Image processing